FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN PILIHAN PASIEN RAWAT INAP DI RUMAH SAKIT SYARIAH RIDHOKA SALMA CIKARANG BARAT - Rohman, Abdul; Ghofar, Abdul (Sekolah Tinggi Ilmu Ekonomi GICI, 2025)
The fulfillment of health services by a country can be measured through the ratio of hospital beds per 1,000 population. The World Health Organization (WHO) sets a standard of 1 bed per 1,000 population, while the Organisation for Economic Co-operation and Development (OECD) recommends an ideal ratio of 4.7 beds per 1,000 population. Hospitals, as healthcare providers, possess potential in the form of resources, management processes, and healthcare service products that must be of high quality and aligned with community needs to remain competitive. Maternity services are provided across various healthcare facilities, ranging from primary care to referral services equipped with basic and comprehensive emergency obstetric and neonatal care (BEmONC and CEmONC). This study aims to analyze factors associated with inpatient choice decisions at RS Syariah Ridhoka Salma, West Cikarang. Data were collected using questionnaires distributed to all inpatients, both online and in person. The results indicate that promotion, location, and service quality are significantly associated with inpatient choice decisions, while healthcare facilities show no significant association.